2012
DOI: 10.1007/s00330-012-2627-7
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography of the chest with model-based iterative reconstruction using a radiation exposure similar to chest X-ray examination: preliminary observations

Abstract: Model-based iterative reconstruction allows detection of pulmonary nodules with ULD-CT with radiation exposure in the range of a posterior to anterior (PA) and lateral chest X-ray.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
119
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(131 citation statements)
references
References 22 publications
6
119
0
6
Order By: Relevance
“…The newest generation of CTs, in combination with iterative reconstruction techniques [14], allow for ultralow-dose CT acquisitions with effective doses similar to the dose of the topogram, and thus, not more than the dose with conventional thoracic radiography in two projections, which is 0.05-0.24 mSv [15]. These ultralow-dose CT acquisitions allow a high sensitivity and diagnostic confidence for the detection of pulmonary nodules [16].…”
Section: Introductionmentioning
confidence: 99%
“…The newest generation of CTs, in combination with iterative reconstruction techniques [14], allow for ultralow-dose CT acquisitions with effective doses similar to the dose of the topogram, and thus, not more than the dose with conventional thoracic radiography in two projections, which is 0.05-0.24 mSv [15]. These ultralow-dose CT acquisitions allow a high sensitivity and diagnostic confidence for the detection of pulmonary nodules [16].…”
Section: Introductionmentioning
confidence: 99%
“…The strength of this study compared to other studies evaluating the use of ASIR and MBIR in conjunction with reduced dose is that it represents a more thorough qualitative and quantitative analysis (including the use of two phantoms) for the specific application of lung cancer screening with a focus on GGO definition 13 , 14 , 15 . Despite the study strengths, there were several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that, even though the apparent difference in the texture of the MBIR images makes it difficult to conduct a blinded reader study, (19) the appearance of MBIR images is reported to have a minimal impact on clinical diagnosis. (19,29,30) In the near future, we plan to conduct a reader study based on the phantom images that we have acquired to evaluate the effect of texture on perception, but it is not within the scope of this study. It must be emphasized that the results presented here apply to the very specific phantom/image acquisition conditions and objects analyzed, and the results may not be readily extrapolated to other situations.…”
Section: Discussionmentioning
confidence: 99%